Personality traits and sex-role schema in adult patients with childhood-onset combined pituitary hormone deficiency not treated with growth hormone (Journal of Medical Science, 2017)
Background. Patients with combined pituitary hormone deficiency have quantitative and qualitative abnormalities of pituitary hormone production that may trigger psychological consequences. Several studies have evidenced symptoms of social disturbances in these patients. Aim. The aim of this study was to evaluate personality traits and psychological sex-role schema influencing social adaptation in patients with childhood-onset combined pituitary hormone deficiency. Material and Methods. Study involved a unique group of 28 adult patients with childhood-onset combined pituitary hormone deficiencies that were never treated with growth hormone. To psychological assessment the short Polish version of Bem’s Sex Role Inventory and the Polish version of Minnesota Multiphasic Personality Inventory were used in the study. Results. The analysis of scores on the Polish version of Minnesota Multiphasic Personality Inventory showed significantly elevated results in the scales for lying, hysteria, psychopathic deviation, hypochondria, and schizophrenia as well as decreased scores in hypomania indicating a number of symptoms of maladjustment in many different areas of life. The short Polish version of Bem’s Sex Role Inventory scores indicated that most of combined pituitary hormone deficiency patients were sex-undifferentiated and no one was androgynous. Conclusions. The sex-role schema and certain personality traits seem to predispose childhood-onset combined pituitary hormone deficiency patients not treated with growth hormone to problems with social adaptation and greater susceptibility to situational stressors. Neurotic reactions, tendency for social alienation, and lack of flexibility have all been observed in these patients. Therefore, combined pituitary hormone deficiency patients may more often need special support when it comes to coping with disease.